2012
DOI: 10.1210/en.2011-2159
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Specific Modulation of Presynaptic Aromatization in the Vertebrate Brain

Abstract: Estrogens affect a diversity of peripheral and central physiological endpoints. Traditionally, estrogens were thought to be peripherally derived transcription regulators (i.e. slow acting). More recently, we have learned that estrogens are also synthesized in neuronal cell bodies and synaptic terminals and have potent membrane effects, which modulate brain function. However, the mechanisms that control local steroid concentrations in a temporal and spatial resolution compatible with their acute actions are poo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 30 publications
2
44
0
Order By: Relevance
“…high but physiological concentration of ATP, magnesium and calcium) (43). The same inhibition has also been described in the HPOA and ovary of female quail, in the telencephalon of male and female zebra finches, as well as in neuronal or non-neuronal cell lines stably expressing human aromatase (47)(48)(49). This enzymatic down-regulation is prevented by blocking the activity of a variety of kinases or by chelating calcium (43,47,48,50), supporting the notion that the rapid control of aromatase activity depends on calcium-depend phosphorylations.…”
Section: Short-term Regulation: In Vitro Studiessupporting
confidence: 52%
See 1 more Smart Citation
“…high but physiological concentration of ATP, magnesium and calcium) (43). The same inhibition has also been described in the HPOA and ovary of female quail, in the telencephalon of male and female zebra finches, as well as in neuronal or non-neuronal cell lines stably expressing human aromatase (47)(48)(49). This enzymatic down-regulation is prevented by blocking the activity of a variety of kinases or by chelating calcium (43,47,48,50), supporting the notion that the rapid control of aromatase activity depends on calcium-depend phosphorylations.…”
Section: Short-term Regulation: In Vitro Studiessupporting
confidence: 52%
“…This enzymatic down-regulation is prevented by blocking the activity of a variety of kinases or by chelating calcium (43,47,48,50), supporting the notion that the rapid control of aromatase activity depends on calcium-depend phosphorylations. Interestingly, data collected from microsomes and synatosomes isolated from the zebra finch telencephalon suggest that this acute modulation of AA by phosphorylating conditions primarily concerns synaptic aromatase rather than microsomal aromatase (mostly located in the cell bodies) (48,51).…”
Section: Short-term Regulation: In Vitro Studiesmentioning
confidence: 70%
“…This phosphorylation-dependent inactivation of AA was also demonstrated in various cell lines transfected with the human aromatase gene as well as in quail ovaries [64]. Work conducted in the zebra finch ( Taeniopygia guttata ) telencephalon indicated that this acute modulation of AA by phosphorylating conditions occurs specifically at the level of synaptic terminals but not in the perikaryon [65]. In vivo dialysis in the auditory cortex of the same species provided converging evidence that glutamate rapidly decreases local estrogen concentrations [66] and this effect results from changes occurring at the level of synapses [67].…”
Section: Box 1 Two Independent Controls Of Aromatase Activitymentioning
confidence: 92%
“…Male zebra finches rely predominantly on the central nervous system for the production of estrogens (Remage-Healey et al, 2008; Schlinger and Arnold, 1992), and, as in humans and other primates, systemic estrogen levels can be persistent following gonadectomy (Adkins-Regan et al, 1990). Available evidence indicates that brain estrogen levels can be precisely and acutely controlled at the level of neuronal synaptic terminals in zebra finches (Cornil et al, 2012b; Peterson et al, 2005; Remage-Healey et al, 2011). Interest has therefore grown in understanding the functional significance of acute estrogen production in the brain of zebra finches.…”
Section: Steroids As Neuromodulators Intrinsic To the Cnsmentioning
confidence: 99%